2016
DOI: 10.1016/j.jprot.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a rhizobia-induced drought stress response strategy in Medicago truncatula

Abstract: Drought stress hampers plant energy and biomass production; however it is still unknown how internal C:N balance and rhizobial symbiosis impact on plant response to water limitation. Here, the effect of differential optimal nitrogen nutrition and root nodule symbiosis on drought stress and rehydration responses of Medicago truncatula was assessed. Two groups of plants were nodulated with Sinorhizobium medicae or Sinorhizobium meliloti--differing in the performance of N fixation; the third group grew in a rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 72 publications
3
55
0
1
Order By: Relevance
“…N‐fixing bacteria and AM fungi have the potential to improve plant growth and alleviate drought stress under water‐limiting conditions . Considering such potential, we aimed at assessing whether inoculation with M. mediterraneum and R. irregularis could improve plant growth, grain yield and protein content under water deficit.…”
Section: Resultsmentioning
confidence: 99%
“…N‐fixing bacteria and AM fungi have the potential to improve plant growth and alleviate drought stress under water‐limiting conditions . Considering such potential, we aimed at assessing whether inoculation with M. mediterraneum and R. irregularis could improve plant growth, grain yield and protein content under water deficit.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, authors found an influence of the Rhizobium symbiosis on the abundance levels of stress responsive proteins prior application of the stress treatment. In subsequent works, plants grown under symbiotic conditions were found to present reduced levels of leaf senescence under drought stress, regardless the efficiency of the Rhizobium strain used (Staudinger et al, 2016). Authors concluded that, besides increased jasmonate biosynthesis and potassium ion concentrations, allocation of reserves to osmolytes and a shift in carbon partitioning from starch to sugar are key responses for the observed symbiont-induced stay-green effect.…”
Section: Proteomics As a Tool To Identify Stress Responses In Legumesmentioning
confidence: 99%
“…Several recent studies have provided broad insights into the systemic effects the legume- Rhizobium symbiotic interaction at the root and, especially, leaf metabolic level (Staudinger et al, 2012, 2016; Desalegn et al, 2016; Turetschek et al, 2016). In all these studies, one of the major response found was related to a significantly induction of the plant translational apparatus and an accumulation of plant proteins involved in stress responses.…”
Section: Proteomics Applied To the Study Of The Legume-rhizobium Symbmentioning
confidence: 99%
See 1 more Smart Citation
“…The major mechanisms consist of increased potassium concentrations, balancing the carbon partitioning between starch and sugars and enhance the reserves of osmolytes during drought. Consequently, in general, nodulated plants recovered more effectively from drought than non-nodulated plants [34]. The experimental work, including the number of microbial species and genotypes to be tested, should be divided into several research units.…”
Section: First Objective: Agronomic Characterization Of Local Germplamentioning
confidence: 99%